The exegesis and polemical use of Ps 110 by Ephrem the Syriac-speaking church father - Botha, Phil J. (Old Testament Essays, 2014)
The interpretation and polemical use of Ps 110 by Ephrem the Syrian (c.306-373 C.E.) are investigated. It seems that Ephrem was hesitant to speculate about the relationship between God the Father and Jesus on the basis of his exegesis of Ps 110, but that he insisted that Jesus is called "Lord" by David in Ps 110:1 and "Son" by God in Ps 2:7, while both Pss 2:7 and 110:3 are witnesses which prove that the Father was the procreator of the Son. These texts are used to refute Arian allegations that Jesus was a creature, but are also understood as prophecies which should have been enough to prevent the Jewish leaders from rejecting their Messiah. Particulars of the crucifixion of Jesus are interpreted by Ephrem polemically as symbolic pointers to the status of the Jewish people and the Church in the fourth century, and Ps 110:1 provides the key to understanding this symbolism.
free